2020
DOI: 10.1108/ijoa-12-2019-1993
|View full text |Cite
|
Sign up to set email alerts
|

Work–life conflict and burnout among working women: a mediated moderated model of support and resilience

Abstract: Purpose Using job demand-control-support (JDCS) model as its foundation, the purpose of this paper is to examine the important, but under-explored, relationship between perceptions of work–life conflict and burnout being mediated and moderated by support systems and resilience among female employees in India. Design/methodology/approach A total of 270 female employees belonging to various sectors such as Information Technology/ Information Technology enabled services, retail, bank and hospitality located in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 117 publications
1
37
0
2
Order By: Relevance
“…Research has shown that the buffer for employees to be able to endure chaotic situations is the support from friends and family. Increased resilience in employees indicates that employees will be able to avoid work burnout due to increased family and friends' support [65]. This finding shows a connection between friends' and family's support, resilience, and employees' work engagement.…”
Section: Mediating Effects Of Resiliencementioning
confidence: 79%
“…Research has shown that the buffer for employees to be able to endure chaotic situations is the support from friends and family. Increased resilience in employees indicates that employees will be able to avoid work burnout due to increased family and friends' support [65]. This finding shows a connection between friends' and family's support, resilience, and employees' work engagement.…”
Section: Mediating Effects Of Resiliencementioning
confidence: 79%
“…The position of women in organisations is a widely researched area, and numerous studies recognised that women face the inequality regime in (gendered) organisations where they progress harder and struggle to achieve the same recognition as men (Gupta and Srivastava, 2020; Mate et al , 2019; Santos and Garibaldi de Hilal, 2018; Grow and Yang, 2018; Alvesson, 2013, 2009; Acker, 2009, 1990). The situation is similar in communication industries with women reporting the inequality and cultural masculinities in journalism and advertising, for example (Mills, 2014, 2017; Crewe and Wang, 2018; Gregory, 2016, 2009; Broyles and Grow, 2010, 2008; Cooke, 2019; Topić, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…26 The lack of support from their spouses in terms of household responsibilities can further contribute to the mental stress of females, which can result in much higher levels of personal burnout among working women. 39,40 In this study among female factory workers, there was a considerable number reporting conflict between work and family (0.7039 ± 0.8581).…”
Section: Conflict Of Priorities Between Work and Familymentioning
confidence: 62%
“…A study among males and females showed that burnout was positively associated with work-to-family conflicts. 39 Among working women, Gupta & Srivastava (2020) showed that burnout was positively associated with work-life conflict, and similarly, the latter was negatively associated with family support. 40 The same was also evident among female pediatricians that showed women were less likely to be successful in balancing their job and other personal responsibilities in life).…”
Section: Conflict Of Priorities Between Work and Familymentioning
confidence: 99%
See 1 more Smart Citation